Someday is not a day of the week - Brennan-Nelson, Denise; O'Malley, Kevin, 1961- (Chelsea, MI : Sleeping Bear Press, 2005)
When asking to go on various outings, Max always receives the answer "Someday" from adults, but with a little help from the days of the week, he discovers where "Someday" lives.
Keywords: Days -- Fiction; Parent and child -- Fiction